The income-happiness nexus: uncovering the importance of social comparison processes in subjective wellbeing - Kraft, Pål; Kraft, Brage (Frontiers in Psychology, 2023)
Introduction: Previous research has established a positive correlation between income and subjective well-being (SWB). This correlation is attributed to income's ability to provide material circumstances and influence one's perceived socioeconomic rank in society, known as subjective socioeconomic status (SES).Objective: This study sought to examine whether social comparison processes could mediate the relationship between income and SWB. Specifically, we aimed to explore the impact of comparing one's current socioeconomic situation to individuals from a similar socioeconomic background (referred to as Comsim) on SWB, based on the similarity hypothesis of social comparison theory.Methods: Data stem from two separate two-wave surveys. Study 1 comprised 588 participants, with 294 men and 294 women; age range 25-60 years; mean age 41.5 years). Study 2 comprised 614 participants, with312 men and 302 women; age range 25-60 years; mean age 43.5 years. In both studies, data on predictors and SWB were collected three months apart.In both study 1 and study 2, bivariate analysis demonstrated a positive correlation between income and SWB. However, multivariate regression models revealed that income did not have a direct effect on SWB. Instead, in both studies, subjective SES and Comsim emerged as significant predictors of SWB, with Comsim being the most influential. Furthermore, our formal mediation analysis indicated that subjective SES and Comsim fully mediated the relationship between income and SWB, when combined. Additionally, in study 2, we found that cognitive factors such as personal This is a provisional file, not the final typeset article control, as well as affective factors like self-esteem, played a mediating role between the social comparison processes and SWB.This study contributes to existing research by emphasizing the importance of two distinct social comparison mechanisms in mediating the relationship between income and SWB.Implications: Theraputic interventions to improve SWB should also consider social comparison processes. From a political standpoint, policies addressing income inequality can mitigate the negative effects of social comparisons on well-being. Providing support to those in lower socioeconomic positions can also enhance SWB.